Initial Trials With Susceptibility-Based and Empiric Anti-H. pylori Therapies in Mongolia - Tsogt-Ochir Byambajav; Namdag Bira; Gotov Choijamts; Duger Davaadorj; Boldbaatar Gantuya; Boldbaatar Gantuya; Tserenchimed Sarantuya; Gidaagaya Sarantuya; Altangerel Enkhtsetseg; Dungubat Erdenetsogt; Adiyasuren Battulga; Tegshee Tserentogtokh; et al. (Frontiers Media S.A., 2019)
Background: Mongolia has a high prevalence of Helicobacter pylori infection and gastric cancer. We conducted a prospective, randomized, single-blind study to evaluate the efficacy of common regimens in Mongolia and to obtain specimens for susceptibility testing.Methods: Empiric treatments: 270 patients with confirmed H. pylori infection were randomized to receive 10 days clarithromycin-triple therapy (Clari-TT) (n = 90), modified bismuth quadruple therapy (M-BQT) (n = 90), or sequential therapy (ST) (n = 90). A second group of 46 patients received susceptibility-based Clari-TT. H. pylori was cultured from 131 patients and susceptibility testing was performed. H. pylori eradication was confirmed by stool antigen 4 weeks after the therapy.Results: Intention-to-treat (ITT) analysis cure rates were 71.1% (95% CI = 61.7-80.5%) for Clari-TT, 87.8% (95% CI = 81-94.6%) for M-BQT, 67.8% (95% CI = 58.1-77.5%) for ST vs. 89.1% (95% CI = 86-98.2%) for susceptibility-based Clari-TT. Per-protocol (PP) analysis results for these therapies were 72.7% (63.4-82%), 89.8% (83.5-96.1%), 68.5% (58.8-78.2%), and 97.6% (89.5-99.8%), respectively. Among 131 cultured H. pylori, resistance rates to amoxicillin, clarithromycin, and metronidazole were 8.4, 37.4, and 74%, respectively.Conclusion: In Mongolia, the prevalence of H. pylori resistance is high requiring bismuth quadruple therapy or susceptibility-based therapy to obtain acceptable cure rates.